Distribution of CPP-Protein Complexes in Freshly Resected Human Tissue Material - Saar, Külliki (Molecular Diversity Preservation International, 2010)
Interest in cell-penetrating peptides (CPPs) as delivery agents has fuelled a large number of studies conducted on cultured cells and in mice. However, only a few studies have been devoted to the behaviour of CPPs in human tissues. Therefore, we performed ex vivo tissue-dipping experiments where we studied the distribution of CPP-protein complexes in samples of freshly harvested human tissue material. We used the carcinoma or hyperplasia-containing specimens of the uterus and the cervix, obtained as surgical waste from nine hysterectomies. Our aim was to evaluate the tissue of preference (epithelial versus muscular/connective tissue, carcinoma versus adjacent histologically normal tissue) for two well-studied CPPs, the transportan and the TAT-peptide. We complexed biotinylated CPPs with avidin-β-galactosidase (ABG), which enabled us to apply whole-mount X-gal staining as a robust detection method. Our results demonstrate that both peptides enhanced the tissue distribution of ABG. The enhancing effect of the tested CPPs was more obvious in the normal tissue and in some specimens we detected a striking selectivity of CPP-ABG complexes for the normal tissue. This unexpected finding encourages the evaluation of CPPs as local delivery agents in non-malignant situations, for example in the intrauterine gene therapy of benign gynaecological diseases.